PENGGUNAAN DIGITAL PAYMENT PADA USAHA MIKRO, KECIL, DAN MENENGAH - Suryanto Suryanto; Herwan Abdul Muhyi; Poni Sukaesih Kurniati (Departemen Ilmu Administrasi Bisnis, Fakultas Ilmu Sosial dan Ilmu Politik, UNPAD, 2022)
This study aims to analyze the transformation of micro, small and medium enterprise (MSMEs) financing in Indonesia. This research is motivated by the phenomenon of MSMEs, which often face problems in financing. However, on the other hand, financial institutions find it difficult to find a database of MSMEs to channel their loans. This study uses a descriptive method with a qualitative approach. Sources of data were obtained from various sources, both primary and secondary. Primary data is obtained from statements made by informants from the Financial Services Authority, the Association of Indonesian Crowdfunding Services, crowdfunding players, and MSMEs that have taken advantage of crowdfunding. Meanwhile, secondary data were obtained from several published articles. The results show that the government has helped provide a source of financing for MSMEs, both through banking and non-banking. However, there were several obstacles that occurred in the field, both from MSMEs and financial institutions. The presence of securities crowdfunding instruments raises new hopes for MSMEs in fulfilling financing. In addition to an easy submission procedure, access can also be done via a digital platform.Penelitian ini bertujuan untuk menganalisis penggunaan digital payment pada Usaha Mikro, Kecil Dan Menengah (UMKM). Metode penelitian yang digunakan adalah kualitatif dengan jenis penelitian eksploratif. Sumber data diperoleh dari hasil wawancara mendalam dan studi literatur. Wawancara dilakukan dengan beberapa informan, antara lain: perusahaan asosiasi fintech, Bank Indonesia, Asosiasi UMKM Indonesia, dan perusahaan pengguna digital payment. Hasil penelitian menunjukkan bahwa penggunaan system pembayaran telah mengalami evolusi sejak jaman barter hingga system digital payment. Penggunaan system digital payment banyak memberikan beberapa manfaat. Adapun manfaat penggunaan digital payment dapat dirasakan baik oleh pelaku usaha sendiri maupun oleh konsumen. Dengan demikian penggunaan digital payment mampu meningkatkan efektivitas dan efesiensi khususnya bagi pelaku UMKM. Kesimpulan dari penelitian ini bahwa penggunaan digital payment mampu meberikan berbagai manfaat bagi pelaku UMKM.